Association of estradiol with sleep apnea in depressed perimenopausal and postmenopausal women: a preliminary study. Issue 1 (January 2017) - Galvan, Thania; Camuso, Julia; Sullivan, Kathryn; Kim, Semmie; White, David; Redline, Susan; Joffe, Hadine
Abstract: Objective: Women's risk of obstructive sleep apnea (OSA) increases substantially during and after the menopausal transition, when depression risk is also elevated, raising the possibility that estrogen withdrawal contributes to OSA vulnerability, in turn contributing to mood disturbance. We examined the association between estradiol levels and OSA in depressed peri- and postmenopausal women. Methods: Thirty depressed peri-/postmenopausal women (mean body mass index [BMI] 30.82 kg/m 2 ) without known OSA completed routine polysomnography concurrent with serum estradiol levels. Estradiol in women with apnea-hypopnea indices (AHI) ≥15 indicating moderate-to-severe OSA was compared against those with AHI less than 15 using logistic regression adjusting for age and BMI. Results: Thirteen women (43%) had AHI ≥15 (median AHI 21.6). Estradiol levels were lower ( P = 0.02) in those with OSA (median 19, interquartile range 9-25 pg/mL) than without OSA (median 29, interquartile range 19-66 pg/mL). On univariate analysis, higher estradiol was associated with reduced odds of OSA (odds ratio 0.95, 95% CI 0.90-0.99, P = 0.04). After adjusting for age and BMI, estradiol levels remained associated with lower odds of OSA (odds ratio 0.90), but the association was no longer statistically significant (95% CI 0.76-1.05, P = 0.18). Montgomery Åsberg Depression Rating Scale scores did not differ between those with and without OSA. Conclusions: These preliminary results suggest that, in addition to higher BMI and age, lower estradiol may be associated with increased OSA risk in depressed women during the peri- and postmenopause, raising the possibility that estradiol withdrawal associated with menopause influences upper-airway patency in women.